2012
DOI: 10.1177/1362168812455588
|View full text |Cite
|
Sign up to set email alerts
|

The congruence of vocational interests and the workplace environment: Reducing the language teacher shortage

Abstract: There is a shortage of second/foreign language (S/FL) teachers in many parts of the world, and the rates of attrition are cause for alarm in North America. Canadian and US teachers' (N = 323) were administered the Self-Directed Search vocational interest inventory and the Coping in Stressful Situations scale. Results from this quantitative study confirmed the vocational profile of an efficacious second/foreign language teacher and revealed significant differences in coping styles between those teachers with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 40 publications
(62 reference statements)
0
27
0
Order By: Relevance
“…Approximately three‐fourths of all CTs were over the age of 40, with 36.2% between the ages of 51 and 60. One significant issue for consideration is the impact of CT retirement on PreK–12 WL programs in light of two challenges: (a) the established WL teacher shortage (Swanson, ) and (b) the precarious status of WL teacher education programs due to budget constraints and low enrollment (García et al, ). As WL CTs retire, who will work with the next, increasingly small number of TCs who plan to enter tomorrow's WL classrooms and teach our PreK–12 learners?…”
Section: Discussionmentioning
confidence: 99%
“…Approximately three‐fourths of all CTs were over the age of 40, with 36.2% between the ages of 51 and 60. One significant issue for consideration is the impact of CT retirement on PreK–12 WL programs in light of two challenges: (a) the established WL teacher shortage (Swanson, ) and (b) the precarious status of WL teacher education programs due to budget constraints and low enrollment (García et al, ). As WL CTs retire, who will work with the next, increasingly small number of TCs who plan to enter tomorrow's WL classrooms and teach our PreK–12 learners?…”
Section: Discussionmentioning
confidence: 99%
“…Also of note are the emotional intelligence research reported in Yin et al. () in education and a study on vocational profiles by Swanson (). All of these studies indicate that individual factors such as personality characteristics and learned coping skills can impact an FL teachers’ ability to balance the emotional demands of the profession.…”
Section: Implications and Conclusionmentioning
confidence: 93%
“…A substantial body of work has investigated teachers' feelings of self-efficacy, and how this impacts students' performance (Swanson, 2012(Swanson, , 2013(Swanson, , 2014. Research has also focused on SE within a motivational framework, or within self-regulation and learning strategies (Chang, 2010;Dörnyei & Otto, 1998;Lee, Yu, & Liu, 2017;Wang & Bai, 2016).…”
Section: Self-efficacy and Slamentioning
confidence: 99%